Pd-Catalyzed One-Pot Borylation/Intramolecular Asymmetric Arylation on α-Ketiminoamides: Innovative Approach to Chiral 3-Amino-2-oxindoles - Marques, Carolina S.; Lawrence, Simon E.; Burke, Anthony J. (Synlett, 2018)
3-Amino-2-oxindole derivatives are a common framework found in many natural products and medicinal compounds and thus their synthesis is of significant importance. We report for the first time a one-pot approach for the synthesis of these compounds, using a borylation/intramolecular asymmetric arylation sequence starting from ortho-bromo-α-ketimino amide derivatives. Pd(OAc)2 was used as the pre-catalyst along with (R)-BINAP as the chiral source. We successfully obtained a family of 3-phenyl-3-(aryl-amino)-indolin-2-one derivatives (11 in total) with excellent yields (up to 98%) and enantioselectivities of up to 76% ee. The reaction is versatile and tolerant of a wide range of functional groups.
Keywords: oxindoles; intramolecular; bis(pinacolate)diboron; palladium; arylation; α-ketimines